ANALISIS KETERAMPILAN CHEST PASS PADA SISWA KELAS X AGRIBISNIS PENGOLAHAN HASIL PERTANIAN SMK NEGERI 1 BAWEN - Sigih Ibad Pramono; Gogot Ardyas Moko (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2026)
This study aims to analyze the chest pass skills of basketball students of class X Agribusiness Agricultural Product Processing at SMK Negeri 1 Bawen because Bawen still has difficulty in passing the ball, especially when passing chest pass to his friends. The study used a quantitative approach with a survey method and an instrument in the form of a chest pass assessment rubric. The research sample was all class X students totaling 35 students. Data The data was analyzed descriptively and presented in the form of a percentage showing that the chest pass ability in the "moderate" category was more than the others, namely 13 students or 37%, then the "Less" category 12 students or 34%, the "Very less" category there were 6 students or 17%, the Good category was 4 students or 11% and the last was the "Very good" category 0 students. The results of the study showed that no students reached the "very good" category and the good category was only 4 students with a standard deviation of 1.81 and the lowest (8) and highest (14) scores. These results indicate that most students still need improvement in their chest pass skills to meet better standards with effective and innovative learning methods to improve students' overall chest pass abilities.